Equity and Population Health: Toward a Broader Bioethics Agenda - Daniels, Norman (The Hastings Center report, 2006)
Bioethics' traditional focus on clinical relationships and exotic technologies has led the field away from population health, health disparities, and issues of justice. The result: a myopic view that misses the institutional context in which clinical relationships operate and can overlook factors that affect health more broadly than do exotic technologies. A broader bioethics agenda would take up unresolved questions about the distribution of health and the development of fair policies that affect health distribution.